Is endurantism really more plausible than perdurantism from a common-sense perspective? - Felletti, Flavia (Praxis Filosófica, 2017)
I will discuss three arguments in favor of perdurantism, the thesis that objects persist by having temporal parts located at different times. Firstly, I will introduce the rival accounts of persistence of perdurantism and endurantism. Then I will discuss three arguments for perdurantism: the problem of temporary intrinsics, the argument from vagueness and the argument from Special Relativity. I will conclude that none of them represents a knock-down argument for perdurantism. However, endurantism faces important difficulties in offering its solutions to the issues at stake, and the solutions proposed are often at odds with commonsense. Therefore, if one of the main problem for perdurantism is its being at odds with commonsense, endurantism is in no better position with respect to this issue.